Polish credit institutions within the European Union: a cross-country survey - Dybał, Mariusz (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The paper presents an analysis of the Polish financial system, with regard to both the number of financial institutions and their assets over the last two decades. Data on the structure of household assets are also presented. According to the study, banks are the most important institutions in the Polish financial system. Analyzed in order to compare Polish credit institutions with all other members of the European Union were total assets of credit institutions, assets of the 25 largest banks in the European Union, as well as in Central and East Europe, share of the five largest credit institutions in total assets (CR5), asset share of credit institutions with majority foreign equity ownership, number of credit institutions, number of local units (branches), number of residents per credit institution local unit, number of employees of credit institutions, assets of credit institutions per employee and GDP per capita in PPS. The data demonstrate that over the past decade Polish credit institutions have largely strengthened their position within the European Union.
Keywords: system finansowy; aktywa gospodarstwa domowego